1978
DOI: 10.1246/bcsj.51.1041
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Absorption Spectra of Single Crystals of Tetrathiafulvalenium Salts

Abstract: The polarized absorption spectra over the range, 5000–37000 cm−1, were observed on the single crystals of the highly-conductive, mixed-valence tetrathiafulvalenium salts, (TTF)Br0.71, (TTF)I0.71, and (TTF)(SCN)0.57, by using a microspectrophotometer. The spectra of these crystals were very similar to each other. The observed spectra were successfully interpreted in terms of the localized model, considering the charge transfer transitions between TTF species and the local excitations associated with the intramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
51
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 26 publications
9
51
1
Order By: Relevance
“…This contact is very short compared to that observed in neutral BMDT-TTF (3.80A; Kato et al, 1985) and even shorter than that observed in the eclipsed dimer of (BMDT-TTF)2Au(CN) 2 (3.635 A; Nigrey, Morosin, Kwak, Venturini & Baughman, 1986). The S..-S contacts in the dimer of (BMDT-TTF)I a are rather close to those observed in the eclipsed dimer of tetrathiafulvalenium perchlorate (TTF)C104 [3.347 (3)-3.555 (3)]k (Yakushi, Nishimura, Sugano & Kuroda, 1980)], which exhibits charge-transfer absorption between the TTF + cation radicals in the near infrared region (Sugano, Yakushi & Kuroda, 1978). The present compound (BMDT-TTF)I a also exhibits an intense absorption band in that region (Sugano & Kinoshita, 1988).…”
Section: 4;3'4'-bis (Methylenedithio)tetrathiafulvalenium Triiodidesupporting
confidence: 59%
“…This contact is very short compared to that observed in neutral BMDT-TTF (3.80A; Kato et al, 1985) and even shorter than that observed in the eclipsed dimer of (BMDT-TTF)2Au(CN) 2 (3.635 A; Nigrey, Morosin, Kwak, Venturini & Baughman, 1986). The S..-S contacts in the dimer of (BMDT-TTF)I a are rather close to those observed in the eclipsed dimer of tetrathiafulvalenium perchlorate (TTF)C104 [3.347 (3)-3.555 (3)]k (Yakushi, Nishimura, Sugano & Kuroda, 1980)], which exhibits charge-transfer absorption between the TTF + cation radicals in the near infrared region (Sugano, Yakushi & Kuroda, 1978). The present compound (BMDT-TTF)I a also exhibits an intense absorption band in that region (Sugano & Kinoshita, 1988).…”
Section: 4;3'4'-bis (Methylenedithio)tetrathiafulvalenium Triiodidesupporting
confidence: 59%
“…The insulating TTF salt, (TTF) 3 (BF 4 ) 2 25 We observe noticeable absorptions for this salt near 0.6 eV which are attributed to intermolecular charge transfer from TTF 0 to TTF +• , as well as an absorption attributed to an intramolecular transition for a lone TTF +• within a dimer at 3.18 eV. 22,24 The weak peaks at 1.5 eV and 2.3 eV are an intradimer transition and an intramolecular TTF +• transition, respectively.…”
mentioning
confidence: 82%
“…Prior work from Sugano et. al 22 and Torrance et. al 23,24 were the main sources used for interpreting the presented spectra.…”
mentioning
confidence: 89%
“…116b) indicates that the intramolecular transitions of TTF þ (400 and 560 nm) are polarized perpendicular to the c-axis and the intermolecular CT band (Band B, 830 nm) is parallel to the c-axis in agreement with the single crystal optical work. 694 The film shows semiconducting behavior, despite its RT conductivity as high as 10 2 -10 3 S cm À1 (==c). The conductivity anisotropy (Fig.…”
Section: Reticulate Doped Polymer (Rdp) Filmsmentioning
confidence: 99%
“…694 The presence of Band A and the absence of Band B show that either the stoichiometry is not exactly 2:1 but the salt is anion deficient (ET) 2 in CH 3 CN. 266 Band A is a transition expressed by Eq.…”
Section: Pt Type and Cation Radical Salt: 33mentioning
confidence: 99%